The Role of Information Technology and Internal Control Systems in Realizing Accountability and Transparency based on ISAK 35 and its Impact on Perceptions of Sustainability of Entity Activities - Lukman Anthoni; Yusuf Yusuf; Asep Suherman (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the influence of Information Technology and Internal Control Systems on Accountability and Transparency based on ISAK 35 and their impact on perceptions about the sustainability of non-profit organization activities. Data was collected through questionnaires distributed to 100 respondents who are non-profit organization stakeholders. The collected data is then processed using the Structural Equation Models method with the help of SmartPLS. The hypothesis test results show that Information Technology has a positive and significant influence on Accountability and Transparency. Increasing the application of Information Technology can potentially increase the accountability and transparency of non-profit organizations. In addition, the Internal Control System also has a positive and significant impact on Accountability and Transparency. Increasing the implementation of the Internal Control System can positively impact the Accountability and Transparency of non-profit organizations. Furthermore, this study also shows that Accountability and Transparency positively and significantly influence the sustainability of non-profit organizations. Accountability also acts as a mediating variable between Information Technology and Internal Control Systems and Sustainability. This indicates that increased Accountability and Transparency can contribute to increasing the sustainability of the activities of non-profit organization entities.